A Comparative Study Of Creative Thinking Levels Among University Students - Salim, Saada; Abdelmalek, Chetiuoi (Journal of Sport Science Technology and Physical Activities, 2025)
This study aims to examine the differences in the level of creative thinking among students of the Institute of Sciences and Techniques of Physical Activities and Sports based on their academic level, and to compare the level of creative thinking between the students of the institute and those of other faculties. The researchers used a descriptive approach, with a sample size of 1639 students selected through stratified random sampling. The Torrance Test of Creative Thinking was adopted to measure creative thinking skills. The results showed that there were no statistically significant differences in the level of creative thinking among students based on their academic level, nor were there statistically significant differences in the level of creative thinking between students of the institute and those of other faculties.